2019
DOI: 10.3847/1538-4357/ab1f8d
|View full text |Cite
|
Sign up to set email alerts
|

An Evolving and Mass-dependent σsSFR–M Relation for Galaxies

Abstract: The scatter (σ sSFR ) of the specific star formation rates (sSFRs) of galaxies is a measure of the diversity in their star formation histories (SFHs) at a given mass. In this paper we employ the EAGLE simulations to study the dependence of the σ sSFR of galaxies on stellar mass (M ⋆ ) through the σ sSFR -M ⋆ relation in z ∼ 0 − 4. We find that the relation evolves with time, with the dispersion depending on both stellar mass and redshift. The models point to an evolving U-shape form for the σ sSFR -M ⋆ relatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 157 publications
13
52
0
Order By: Relevance
“…The new constraint minimally affects the EAGLE-SKIRT sample, because almost all galaxies in the selected mass bin already have the sSFRs above −10.8 yr −1 . This is in agreement with Katsianis et al (2019), who found the fraction of only ≈ 0.1 early-type galaxies at similar M star and sSFRs, for the whole EAGLE reference simulation, at z = 0. The results are shown in bottom panels of Fig.…”
Section: The Galaxy Populationsupporting
confidence: 92%
“…The new constraint minimally affects the EAGLE-SKIRT sample, because almost all galaxies in the selected mass bin already have the sSFRs above −10.8 yr −1 . This is in agreement with Katsianis et al (2019), who found the fraction of only ≈ 0.1 early-type galaxies at similar M star and sSFRs, for the whole EAGLE reference simulation, at z = 0. The results are shown in bottom panels of Fig.…”
Section: The Galaxy Populationsupporting
confidence: 92%
“…We present a detailed comparison to previous observations (Noeske et al 2007 ;Guo, Zheng & Fu 2013 ;Guo et al 2015 ;Ilbert et al 2015 ;Schreiber et al 2015 ;Willett et al 2015 ;Boogaard et al 2018 ), the EAGLE hydrodynamical simulations (Matthee & Schaye 2018 ;Katsianis et al 2019 ) and Shark semi-analytic model (Lagos et al 2018 ) in the Appendix, which is summarized in Fig. 8 .…”
Section: The σ Sfr -M Relation For Just the Sfsmentioning
confidence: 86%
“…Sparre et al ( 2015 ) use the Illustris simulation (Vogelsberger et al 2014 ) to explore the SFS and at z ∼ 0 find a relatively flat σ SFR -M at 9 < log 10 [ M * /M ] < 10.5 and increasing dispersion to higher masses, roughly consistent with observations. Katsianis et al ( 2019 ) applied a similar approach to EAGLE (Crain et al 2015 ;Schaye et al 2015 ;McAlpine et al 2016 ;Matthee & Schaye 2018 ) and find a 'U-shaped' σ SFR -M relation similar to that of Willett et al ( 2015 ). Conversely, Matthee & Schaye ( 2018 ) undertake a similar study with EAGLE but find a linearly decreasing σ SFR -M with stellar mass.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…To infer stellar masses from the EAGLE+SKIRT galaxies, we use the Fitting and Assessment of Synthetic Templates (FAST) code (Kriek et al 2009) to fit the mock SEDs, following a similar procedure as various observational studies (González et al 2012;Botticella et al 2017;Aird et al 2018). Following the same procedure as in Katsianis et al (2019) we use the Bruzual & Charlot (2003) stellar population synthesis models and assume an exponentially declining SFH [SFR = exp(−t/tau)] (Fumagalli et al 2016;Abdurro'uf 2018), the Chabrier IMF (Chabrier 2003), the Calzetti et al (2000) dust attenuation law (Cullen et al 2018;McLure et al 2018b) and a metallicity Z = 0.2 Z⊙ (Chan et al 2016;McLure et al 2018a). We note that these assumptions are motivated by observational studies but not necessarily stand neither for the real/observed nor the EAGLE+SKIRT simulated galaxies (in table 1 we sumarize the SED fitting assumptions used by different authors).…”
Section: Stellar Masses and Sfrs From The Eagle+skirt Datamentioning
confidence: 99%